THE DEVELOPMENT OF LOCAL LEARNING ACTIVITIES ACCORDING TO THE STEM EDUCATION APPROACH TO PROMOTE SCIENTIFIC SKILLS AND CREATIVE THINKING PROCESS FOR JUNIOR HIGH SCHOOL STUDENTS IN LAMPANG - Kaewkongpan, Duangjan; Phosri, Wiphawadee Phosri; Saiopparach, Tunyawan; Choothong, Chisapath; Khamhaeng, Amporn (Journal of Education and Innovation, 2024)
The objectives of this research were to 1) design a local learning activity based on STEM education for junior high school students, 2) study scientific process skill development for junior high school students who received local learning activities based on STEM education, and 3) study the creativity of junior high school students who has been organized the local learning activities based on STEM education. This research was a one-shot case study. The sample used in the research was selected by purposive, 14 students who studying in Mathayomsuksa 1 at a school in Mae Ta District, Lampang Province. The tools used in the research were; 1) a local learning management plan based on STEM education consisting of an upside-down tomato planting miracle activity, and tomato processing activities, 2) an integrated scientific process skills assessment form, and 3) creativity assessment form. The statistics used to analyze the data were mean and standard deviation. The research results showed that: 1. The results of the design of local learning activities based on STEM education. It was an integration of science teaching that was consistent with the local context where tomato cultivation is the main occupation in the community. There were 6 STEM education learning activities as follows: 1) problem Identification, 2) related Information searching, 3) solution design, 4) planning and development, 5) testing, evaluation and design improvement, and 6) presentation. 2. Integrated scientific process skills after receiving local learning activities according to STEM education in all 5 skills, including hypothesis, defining the operational definition of a variable, defining and controlling variables, experimenting and interpreting data, and conclusions, at a good level. 3. The creative thinking after receiving local learning activities according to STEM education in all 4 aspects, including fluent thinking, flexible thinking, originality and meticulous thought, at a good level.